Penatalaksanaan Holistik Pada Anak Usia 11 Tahun dengan Tonsilitis Kronik Melalui Pendekatan Kedokteran Keluarga - Hadijah, Nur Ashianty; Dahlia, Dahlia; Marimba , Andi Darwin (Universitas Pahlawan Tuanku Tambusai, 2025)
Chronic tonsillitis is a medical condition that is often found in primary care, with significant health impacts on sufferers. This study aims to analyze the management of chronic tonsillitis with a holistic diagnostic approach at Cendrawasih Health Center. This case study involved an 11-year-old patient who was diagnosed with chronic tonsillitis based on anamnesis and physical examination. The epidemiological triad in this case includes agent factors in the form of allergens, hosts (patients), and environmental factors including the habit of consuming cold drinks and chewing ice cubes. The management provided includes drug therapy with penicillin antibiotics and surgery (tonsillectomy). In addition, education for patients and families is very important in increasing knowledge about regular treatment, lifestyle modification, and family motivation to support the treatment process. The patient's psychosocial diagnosis showed concerns about difficulty breathing that could lead to death and fear that the disease would not be cured. This study emphasizes the importance of a holistic approach in the management of chronic tonsillitis, which not only focuses on physical treatment but also pays attention to the patient's psychosocial aspects.